Integrated Teaching: the Need of the Hour (Bangladesh Journal of Medical Education, 2022)
Integration means a systemic organization of teaching matter pertaining to different disciplines coordinating delivery of the learner to give a holistic approach to medical study. The objective of this study is to compare the effectiveness of integrated with traditional teaching. Twenty integrated and ten traditional sessions were conducted over five semesters. Duration of each session was 90 minutes. Sample sizes for integrated and traditional groups were respectively 5600 and 1400 students. Pre and post- test scores for integrated, pre and post- test scores for traditional and post-test scores for integrated and traditional teaching groups were compared. Faculty and students’ feedback were analyzed. Difference in Pre and Post-Test scores for integrated teaching was statistically highly significant. Difference in Pre and Post-Test scores in traditional teaching group, though statistically significant, was less than that observed with integrated teaching .The difference in Post-Test scores obtained in integrated and traditional teaching groups was statistically highly significant. Ninety four percent Faculties agreed that integrated teaching was an effective mode of training. Ninety percent faculties rated the program on a higher scale. Ninety five percent students liked the concept of integrated teaching. .Student-centered, patient-oriented approach is the fruitful outcome of the integrated teaching model, which will definitely help us to have a much needed “Basic Doctor.”Bangladesh Journal of Medical Education Vol.13(1) January 2022: 79-86